Penerapan Metode Design Thinking Dalam Perancangan UI/UX Sistem Pencatatan dan Pemantauan Kekeruhan Air Berbasis Website - Efansa, Chika; Chika Efansa; Pradita Eko Prasetyo Utomo; Muhammad Razi A (STEKOM PRESS, 2025)
PAMTIRTA Tempino is an institution that provides clean water services in the Tempino area. The process of recording water use and monitoring water turbidity is still done manually, making it prone to recording errors and making it difficult to monitor the water quality distributed to the community. This study aims to design a website-based water turbidity recording and monitoring system by focusing on User Interface (UI) and User Experience (UX) aspects using the Design Thinking method. The research follows five stages of Design Thinking: empathize, define, ideate, prototype, and test. Data collection involves observation and in-depth interviews with PAMTIRTA officers. The results include a design with key features such as digital water meter recording, turbidity monitoring dashboards, and complaint services. The prototype was tested using Maze and the System Usability Scale (SUS), achieving a score of 80.1 and falling into the